2020
DOI: 10.1002/cpp.2539
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of a specialized therapy programme for burnout using subjective report and biomarkers of stress

Abstract: The increasing prevalence of stress‐related disorders such as burnout urges the need for specialized treatment approaches. Programmes combining psychotherapy and regenerative interventions emerge to be the most successful. However, evaluated therapy programmes are scarce and usually involve subjective symptom quantification without consideration of physiologic parameters. The aim of the present exploratory, single‐group study was the multimodal investigation of the effectiveness of a specialized holistic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In a naturalistic study by Orosz et al [ 54 ], 71 patients were treated for depression, either single episode or recurrent, with comorbid burnout syndrome. A six-week therapeutic program was followed that involved individual CBT therapy, group therapy, and other therapeutic methods, most notably physical exercise in various forms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a naturalistic study by Orosz et al [ 54 ], 71 patients were treated for depression, either single episode or recurrent, with comorbid burnout syndrome. A six-week therapeutic program was followed that involved individual CBT therapy, group therapy, and other therapeutic methods, most notably physical exercise in various forms.…”
Section: Resultsmentioning
confidence: 99%
“…The available evidence on the association of psychotherapy and change in BDNF protein levels in plasma or blood serum is inconsistent. In most cases, studies have shown that there were no statistically significant changes in the BDNF concentration levels; only the studies by Orosz et al [ 54 ], Yamada et al [ 46 ], and Zwipp et al [ 48 ] proved otherwise. However, in the case of AN patients, BDNF increase was linked to body weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF plays a critical role in development and plasticity of the brain and is implicated in the pathology of many psychiatric disorders ( 68 ). Several studies have now reported that CBT and other behavioral therapies can increase peripheral levels of BDNF ( 69 , 70 ). For example, one recent study found that CBT for chronic stress increased serum levels of BDNF, in addition to improving sleep, depressive symptoms, and emotional exhaustion ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now reported that CBT and other behavioral therapies can increase peripheral levels of BDNF ( 69 , 70 ). For example, one recent study found that CBT for chronic stress increased serum levels of BDNF, in addition to improving sleep, depressive symptoms, and emotional exhaustion ( 70 ). Some evidence suggests that serum levels of BDNF correlate with markers of neuronal integrity in the CNS ( 71 ).…”
Section: Discussionmentioning
confidence: 99%